2022
DOI: 10.1177/11786388221130560
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Medically Supervised Prolonged Fasting Therapy on Vitamin D, B12, Body Weight, Body Mass Index, Vitality and Quality of Life: A Randomized Control Trial

Abstract: Background: Recent research indicates prolonged fasting for more than 7 days is beneficial in priming the vitamin D metabolism. However, methodological limitations in previous studies, such as insufficient sample size and a lack of control group, limits its generalizability. The present study evaluated the impact of prolonged fasting (10 days) on vitamin D, vitamin B12, body mass index (BMI), weight, hemoglobin, vitality and quality of life (QoL) compared to a normal diet. Methods: This randomized control tria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 26 publications
0
7
1
Order By: Relevance
“…Our findings differ from two of our previous studies on fasting, where we found no significant change in the study participants' hemoglobin levels [ 8 , 9 ]. However, those studies are limited by sample size issues or patient heterogeneity.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Our findings differ from two of our previous studies on fasting, where we found no significant change in the study participants' hemoglobin levels [ 8 , 9 ]. However, those studies are limited by sample size issues or patient heterogeneity.…”
Section: Discussioncontrasting
confidence: 99%
“…We observed a significant increase in the vitamin D levels of the MSF group post-fasting. Earlier research also suggested that fasting under medical supervision could improve vitamin D levels in both healthy volunteers and patients with chronic diseases [ 8 , 9 ]. The present finding substantiates the earlier reports on fasting and vitamin D levels.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Earlier studies also reported MSF up to 10 days can improve the vitamin D levels. 11 12 13 A growing body of literature suggests the role of vitamin D in improving type 2 diabetes-related clinical outcomes by attenuating insulin resistance and priming the endocrine functions of the pancreas. 2 4 5 A meta-analysis study revealed the beneficial effect of vitamin D in reducing fasting blood sugar, glycated hemoglobin levels (HbA1C), and insulin resistance (HOMA-IR) in patients with diabetes mellitus and deficient vitamin D status.…”
Section: Discussionmentioning
confidence: 99%
“…8 Therapeutic fasting has been shown to increase vitamin D levels in both healthy volunteers and chronic disease patients. [11][12][13] However, the role of therapeutic fasting in improving the vitamin D levels in T2DM patients is less understood. The present observational study is therefore intended to explore if the 10-day medically supervised fasting (MSF) has any potential impact on vitamin D, vitamin B12, fasting blood sugar levels, anthropometric measures, quality of life, and disease perception in T2DM patients.…”
Section: Introductionmentioning
confidence: 99%